Literature Review: Analisis Khasiat Tanaman Pala (Myristica Fragnans Houtt) dalam Pengobatan Halitosis Oleh Bakteri - Saeful Amin; Naila Naziba; Hayuning Putri Ambi; Salsabila Sasikirana (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Halitosis, or bad breath, is a multifactorial condition that is often caused by anaerobic bacterial activity in the oral cavity, especially on the dorsum surface of the tongue. The use of natural ingredients as an alternative halitosis treatment is a concern, one of which is the nutmeg plant (Myristica fragrans), which has various active compounds such as essential oils, saponins, flavonoids, and alkaloids. This study aims to assess the potential of nutmeg plants in inhibiting the growth of bacteria that cause halitosis through a literature review of 30 national and international journals within the last five years. The results showed that nutmeg extracts, both from seeds, pulp, and leaves, have antibacterial activity against various types of halitosis-causing bacteria such as Streptococcus mutans, Staphylococcus aureus, and Escherichia coli. This activity is obtained through the mechanism of cell membrane damage and inhibition of bacterial cell wall synthesis by bioactive compounds in nutmeg plants. Therefore, nutmeg has potential as a natural antibacterial agent in the management of halitosis.